Developing The Diffusion Innovation in Transaction Adoption Based on Blockchain Networks: SEM – Neural Network Empirical Study - Audi Ramadhan; Hanifah; Cucu Hayati (CV ODIS, 2022)
This research is aimed to examine the effect and relative importance of diffusion of innovation characteristics, perceived cost, and financial literacy in using blockchain network transactions. This research collected 100 data from a questionnaire of blockchain network users and analyzed using SEM–PLS and Neural Network. SEM–PLS in this research aims to analyze an independent variable's effect on a dependent variable. At the same time, the neural network is used to measure the relative importance of each independent variable on a dependent variable. The result of this research in SEM–PLS shows that compatibility, relative advantage, and perceived cost have a significant effect. In contrast, complexity and financial literacy do not significantly affect the intention to use a blockchain network. Furthermore, the result of the neural network shows that relative advantage is the most important variable in affecting the intention to use of blockchain network, followed by perceived cost and compatibility.